PELAKSANAAN PEMBELAJARAN SENI DRAMA SEJAK USIA DINI - Sumaryadi - (Imaji, 2006)
Regarding the implementation of art education in schools, it is seen that art performance education is put in the third position after visual arts and literature. Among other forms of art performance, drama’s position is under music and dance. Drama is a performance delineating human life, which is acted on stage in front of public. The story generally has conflicts, performed through movements, actions and dialogs. Drama needs introducing to children. The attempts to introduce drama to children should be done as early as possible since the early ages have appropriate space and time, which are strategic to implant basic values in children. Related to this, there are at least two things to be put into consideration. The first is related to literature and the second to art performance. The former covers the determination of theme, synopsis, characters and characterization, plot, dramatic conflict, setting and language use. The latter includes script writing, directing, producer, technical staff, players, and audience. Keywords: art education, drama, early ages